First records of Hamacantha species from seamounts off eastern Australia (Porifera, Demospongiae, Merliida), with description of four new species - Ekins, Merrick; Baker, Soraya; Hooper, John N.a. (Zootaxa, 2023)
Four new species of encrusting Hamacantha (Vomerula) are described from bathyal depths of seamounts off Queensland and Tasmania in southeast Australia (H. (V.) novacula sp. nov., H. (V.) melliflura sp. nov., H. (V.) ridleyi sp. nov., H. (V.) levii sp. nov.). A previously described species known only from New Caledonia (H. (V.) acerata Lévi, 1993) has also been redescribed. A tabular comparison of all known species of H. (Vomerula) is provided, bringing the number of known species in the subgenus to 26. This is also the first record of the genus Hamacantha from the Australian Exclusive Economic Zone.